Electrical Properties of La-Doped Ba0.7Ca0.3TiO3Lead-Free Ceramics - Panupong Jaiban (2018)
© 2015 Taylor & Francis Group, LLC. (Ba 0.7 Ca 0.3 )1-1.5 x La x TiO 3 ceramics with x = 0 - 0.03 were prepared using a solid state sintering method. Upon La 3+ increasing content, tetragonality of doped ceramics decreased. The intrinsic contribution affected piezoelectric coefficient decrement. The changes in dielectric loss, remanent polarization, coercive field, planar electromechanical coupling coefficient and mechanical quality factor seemed to be correlated with the extrinsic contribution from domain wall mobility. La 3+ addition caused both grain size reduction and dielectric constant enhancement. The results here suggested that BCT electrical properties' dependence on La 3+ substitution may be useful for ferroeletric devices.